Development of Character-Based Science Teaching Materials Using the Webbed Model to Improve Students' Creative Thinking Skills - Abdul Haling; Sudirman Sudirman; Nasruddin Nasruddin; Syamsuddin Syamsuddin; Abdul Halik (Universitas Negeri Makassar, 2022)
This study aimed to develop character-based Natural Science teaching materials to improve students' creative thinking skills. The research design is development research with procedures, namely initial information collection, designing, development, assessment, product revision, and dissemination and implementation. The teaching material products assessment was the text of character-based Natural Science teaching materials, guidebooks, and student worksheets. Products assessment was carried out in three stages of assessment, namely the assessment of validity, practicality, and effectiveness. The research has lasted for two years. The product testing subjects were 5 experts and the field trial subjects were the first-grade teachers and students in five elementary schools in Bone regency, South Sulawesi, Indonesia. The data collection was conducted through validation questionnaires for teaching materials, teacher and student response questionnaires, interview guides, and learning outcomes test. The data which was obtained consist of qualitative and quantitative. The data analysis descriptive through validity, practicality, and effectiveness analysis. The results of the study showed that those teaching materials are valid, practical, and effective. In doing so, they can be disseminated and implemented to improve student creative thinking skills in elementary school.